2012
DOI: 10.1155/2012/786494
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Manifestations of Alzheimer’s Disease in Animal Models

Abstract: Alzheimer's disease (AD) is the most common form of dementia, and the pathological changes of senile plaques (SPs) and neurofibrillary tangles (NFTs) in AD brains are well described. Clinically, a diagnosis remains a postmortem one, hampering both accurate and early diagnosis as well as research into potential new treatments. Visual deficits have long been noted in AD patients, and it is becoming increasingly apparent that histopathological changes already noted in the brain also occur in an extension of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 131 publications
1
39
0
1
Order By: Relevance
“…Studies have shown that the cognitive impairment in Alzheimer's disease as determined by mini-mental status examination has a positive correlation with the reduction in macular volume (Parnell et al 2012). In the patients with mild cognitive impairment, which is an early stage of Alzheimer's disease, significant reduction in the retinal nerve fibre layer has been shown in studies (Iseri et al 2006).…”
Section: Results Of Review Of Systematic Evidencementioning
confidence: 99%
“…Studies have shown that the cognitive impairment in Alzheimer's disease as determined by mini-mental status examination has a positive correlation with the reduction in macular volume (Parnell et al 2012). In the patients with mild cognitive impairment, which is an early stage of Alzheimer's disease, significant reduction in the retinal nerve fibre layer has been shown in studies (Iseri et al 2006).…”
Section: Results Of Review Of Systematic Evidencementioning
confidence: 99%
“…Other transgenic mice models have suggested that the inner plexiform layer may be a more sensitive biomarker for detecting AD-related changes compared with RGCs, 70,80 making it difficult to draw firm conclusions. 102 However, both human and mouse studies suggest that AD-related pathology is seen in the retina. RGC loss may be a useful biomarker for assessing the neurodegenerative processes in AD, whether it reflects local pathology or reflects global loss of cortical neurons.…”
Section: The Ganglion Cell Layer In Admentioning
confidence: 99%
“…This was further validated by other independent studies on AD patients [1, 113, 178] that parallel findings in animal models of the disease. The latter, predominantly involving transgenic (Tg) rodents, reported similar retinal patterns, where Aβ deposits often colocalize with sites of apoptosis, neuroinflammation, impairments of function and structure, and plaque formation that even precedes that seen in the brain [46, 107, 108, 139, 148, 149, 152]. …”
Section: Introductionmentioning
confidence: 99%